Translocation of Epipelic Biofilms and Their Short-Term Responses to Urbanization Impacts in Nutrient Rich Streams - Cochero, Joaquín (2021)
Stream biofilms are among the first to react to environmental degradation, since their structural and functional characteristics are tightly linked to the physicochemical variables in the water and sediment. The objectives of this research were to study the differences in chlorophyll-a, bacterial density and metabolism endpoints of epipelic biofilms in nutrient-rich streams under different physical-chemical conditions in the stream water in relation to changes in urbanization, and to measure the short-term responses (up to 72 h) in the biofilm when translocated to more urbanized sites. For these purposes, chlorophyll-a, bacterial density, biofilm respiration (electron transfer activity) and O2 consumption were measured in epipelic biofilms in nutrient-rich streams exposed to different levels of urbanization after a 30 day colonization. Afterward, biofilms were translocated downstream to more polluted sites, and sampled to identify any fast occurring changes to be considered as potential indicators of environmental degradation. Results show that in the nutrient-rich streams studied, the structural characteristics of the biofilm were linked to urbanization, and even after a short time following the translocation, chlorophyll-a and bacterial density varied, reflecting the environmental degradation. On the other hand, metabolic variables were highly variable and produced inconsistent results when representing an increase in urbanization.